Hydroxylysine deficiency, conspicuous skeletal lesions and a strange burial practice in a historical German island population. (24th March 2018) - Burkhardt, A.; Grupe, G.
Abstract: Eighty‐two complete and partial human skeletons were excavated from a burial site on the island of Borkum in the North Sea. The site covers a period of 400 years from the middle of the 14th century AD until 1720 AD. The position of the skeletons in situ suggests rapid disposal of the bodies. About 75% of the skeletons were male and of a quite robust constitution, and about 60% of all individuals died rather young between 20 and 40 years of age. All male skeletons exhibited particular pathological alterations as a result of the typical daily activities of seafaring men, including severe degenerative joint disease and pronounced osteochondropathies. In juvenile skeletons, these pathologies were accompanied by inflammatory processes without exception. Palaeodietary reconstruction by stable isotope analysis resulted in a protein rich diet, confirming fishing as an important part of the subsistence economy. The juveniles derived substantially more protein from plant food than the adults. Bone collagen amino acid profiles were short of hydroxylysine, suggesting that the conspicuous pathological lesions could also have been caused by a systemic connective tissue disease. Possible etiology of the disease is discussed and related to both the uneven sex ratio of the inhumations and the burial context.